2019
DOI: 10.3390/w11040781
|View full text |Cite
|
Sign up to set email alerts
|

Removal Efficiency and Mechanism of Cr(VI) from Aqueous Solution by Maize Straw Biochars Derived at Different Pyrolysis Temperatures

Abstract: The removal efficiency and mechanism of Cr(VI) removal from aqueous solution on semi-decomposed maize straw biochars pyrolyzed at 300 to 600 °C were investigated. The removal of Cr(VI) by the biochars decreased with pyrolysis temperature increasing from 300 to 600 °C, and the maximum removal capacity of Cr(VI) for maize straw biochar pyrolyzed at 300 °C was 91 mg/g at pH 2.0. The percentage removal of Cr(VI) rapidly decreased with pH increasing from 2.0 to 8.0, with the maximum (>99.9%) at pH 2.0. The varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 25 publications
4
26
0
Order By: Relevance
“…This characteristic decides about the potential applications of biochar. Available literature confirms that biochars produced from bio-waste, due to their properties-such as porous structure, high specific surface area and abundant functional groups, have been widely used to remove toxic metals from wastewater [6,8,12,14,30].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This characteristic decides about the potential applications of biochar. Available literature confirms that biochars produced from bio-waste, due to their properties-such as porous structure, high specific surface area and abundant functional groups, have been widely used to remove toxic metals from wastewater [6,8,12,14,30].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Jung et al (2016) also observed this phenomenon for biochar produced at 200, 400, 600 and 800 • C from marine brown macroalga Undaria pinnatifida [13]. The ash content significantly increases with pyrolysis temperature mainly due to the minerals forming ash, which remain after biochar carbonization [30].…”
Section: Yield Of Algal Biochar and Its Proximate Analysismentioning
confidence: 88%
See 2 more Smart Citations
“…However, the modified peat exhibited a greater adsorption efficiency to Cr(VI) than the natural peat. Therefore, based on the above results, it is suggested that chemisorption dominated the adsorption process [1,40,42].…”
Section: Characterization Of Peat Samplesmentioning
confidence: 86%